SIMULASI PRODUKSI GAS SINTESA MELALUI PROSES BIOGAS STEAM REFORMING DENGAN KATALIS Ni/MgO-Al2O3 DAN Ni/La2O3-Al2O3 - Firmansyah, Muhammad Rafli; Silviyati, Idha (Politeknik Negeri Sriwijaya, 2020)
A renewable energy system to produce electricity from biogas feed by integrating the reforming process with an SOFC (Solid Oxide Fuel Cell) was evaluated through experimental and modeling study. The system performance was evaluated using the Aspen Plus process simulation tool and through biogas steam reforming experiments over 10 wt% Ni/MgO-Al2O3 and Ni/La2O3-Al2O3. Biogas steam reforming simulations were conducted for biogas feeds with CH4/CO2 ratios of 40/60, 50/50 and 60/40 at S/C ratios of 1.00–2.00 over a temperature range of 873–1123 K. The experimental data conclude that positive CO2 conversion was attained at temperatures higher than 1073 K. The results show that the proposed system can provide a viable approach to maximizing renewable methane resources for localized power generation